Successful Epidural Anesthesia Management in Cesarean Section for a Patient with Eisenmenger Syndrome: A Case Report - Abdi Kumala; Novita Anggraeni; Sony (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Eisenmenger syndrome is a rare and complex condition that poses significant challenges for anesthesiologists during pregnancy, particularly during labor and delivery. The physiological changes associated with pregnancy, such as increased cardiac output and blood volume, can exacerbate the hemodynamic instability in these patients. Careful selection of anesthetic techniques and agents is crucial to maintain hemodynamic stability and ensure the safety of both mother and fetus. Case presentation: We present the case of a 34-35-week pregnant woman with Eisenmenger syndrome who underwent a successful cesarean section under epidural anesthesia. The patient's hemodynamic parameters were closely monitored throughout the procedure, and no significant complications were encountered. Conclusion: This case report demonstrates that epidural anesthesia can be a safe and effective option for cesarean section in patients with Eisenmenger syndrome. Meticulous planning, close monitoring, and prompt management of potential complications are essential for a successful outcome.